Fiscal Rules for Resource Windfall Allocation : The Case of Trinidad and Tobago - Primus, Keyra (IMF Working Papers; Working Paper ;, 2016)
Managing resource revenues is a critical policy issue for small open resource-rich countries. This paper uses an open economy dynamic stochastic general equilibrium model to analyze the transmission of resource price shocks and a shock to resource production in the Trinidad and Tobago economy. It also applies alternative fiscal rules to determine the optimal allocation of resource windfalls between spending today and saving in a sovereign wealth fund. The results show that spending all the resource windfall on consumption and investment creates more volatility and amplifies Dutch disease effects, when compared to the case where all the excess revenues are saved. Also, neither a policy of full spending nor full saving of the surplus revenue inflows is optimal if the government is concerned about both household welfare and fiscal stability. In order to minimize deviations from both objectives, the optimal fiscal response suggests that a larger fraction of the resource windfalls should be saved.